PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA (SATUAN POLISI PAMONG PRAJA PROVINSI SULAWESI SELATAN) - Ahmad Muwaffaq; Muhammad Yunus Amar; Ria Mardiana Yusuf (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
The success or failure of an organization depends on the activity and creativity of its human resources. For this reason, the main thing to consider is the role of a leader. The role of leadership is very large in motivating employees to work in accordance with work programs that have been set by the organization, in achieving the goals and objectives set by the organization. This study aims to determine and analyze the effect of transformational leadership style, and work environment on job satisfaction, to know and analyze the effect of transformational leadership style and work environment on employee performance, to find out and analyze the effect of job satisfaction on employee performance, and to find out and analyze the influence of transformational leadership style and work environment on employee performance through employee job satisfaction in the Civil Service Police Unit of South Sulawesi Province. To achieve these objectives, data collection techniques are carried out through observation and questionnaire distribution, using data analysis techniques namely descriptive analysis, validity and reliability testing, classical assumption tests, and path analysis. The results prove that the transformational leadership style and work environment have a positive and significant effect on employee job satisfaction. The effect of transformational leadership style and work environment on employee performance. The effect of job satisfaction provides a significant influence in improving employee performance. Mediation test results of the influence of transformational leadership style and work environment on employee performance through job satisfaction which shows that employee job satisfaction can mediate the influence of transformational leadership style and work environment on employee performance of the South Sulawesi Province Civil Service Police Unit.